Hydrogen-Blended Combustion Technology in Gas Turbine - Xiaolong LI; Xiaofei HONG; Yuqing CHEN (南方能源建设, 2023)
[Introduction] As the country has set ambitious targets in carbon peaking and carbon neutrality for the energy sector, there is a growing demand for technology improvements of low-carbon emission for power station gas turbines. It is urgent to explore the path of the key technology for this goal in China. The lean premixed combustion technology of gas turbine can make the air volume for combustion deviate from the theoretical air volume, which is the main technology to reduce NOx emission at present. At the same time, by mixing hydrogen in natural gas when combusting, it can effectively reduce the consumption of fossil energy and reduce carbon emissions. [Method] In this paper, a one-dimensional premixed free propagation flame model was established by Chemkin-Pro software, and the effects of different equivalent ratios, initial temperatures, initial pressures, and hydrogen-blended ratios on combustion temperatures, combustion rates, pollutant generation concentration, combustion free radicals, and chain reactions were compared. The temperature distribution, fuel component change and emission characteristics of combustion process were simulated. [Result] It is found that by mixing hydrogen in natural gas when combusting, fossil energy consumption and carbon emissions can be effectively reduced. However, the higher flame temperature brought by the lean premixed combustion of natural gas mixed with hydrogen will promote the generation of NOx, and at the same time, more CO will be produced at a lower equivalent ratio. [Conclusion] Based on the above research, the key data of hydrogen-blended combustion are obtained, which lays a foundation for the completion of hydrogen-blended combustion technology route.